Pendampingan Pembuatan Kompos Sampah Organik Melalui Compost Bag Bagi Masyarakat Desa Grogol Kabupaten Ponorogo - Faradisya Ekapti, Rahmi; Hakim, Lukman (Amaluna: Jurnal Pengabdian Masyarakat, 2023)
The village of Grogol is one of the villages located in the district of Sawoo, Kabupaten Ponorogo, which has the problem that there is already a compost bag available but it has not been implemented according to its use. Compost bag as a medium in the organic waste processing program to be used as compost distributed by the Government of Ponorogo Regency. However, this waste management program has not been implemented, and the distribution of compost bags is uneven. Starting with the assets of the waste processing program, it is necessary to hold service activities in the form of accompanying composite manufacturing with compost bags. This supporting activity consists of socialization, accompanying compost manufacturing, monitoring, and application of compost products that are only focused on the Kalisobo District. The target support consists of 20 people, namely 15 people who are the heads of each RT and 5 people from the citizenry. Based on the results of the evaluation, it was determined that 15%, i.e., as many as 3 people, can produce finished composite; 35%, that is, 7 people, can produce semi-finished composite; and 50%, that is, 10 people, can produce unfinished compost. And as is expected in the future, the compost manufacturing efforts to reduce this organic garbage will continue and expand thoroughly.